2012
DOI: 10.1002/nbm.2892
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of hyperpolarized 13C‐metabolites in tumor cell spheroids using real‐time NMR spectroscopy

Abstract: The detection of tumors noninvasively, the characterization of their progression by defined markers and the monitoring of response to treatment are goals of medical imaging techniques. In this article, a method which measures the apparent diffusion coefficients (ADCs) of metabolites using hyperpolarized (13) C diffusion-weighted spectroscopy is presented. A pulse sequence based on the pulsed gradient spin echo (PGSE) was developed that encodes both kinetics and diffusion information. In experiments with MCF-7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 43 publications
4
56
0
Order By: Relevance
“…Given the previously described connection between reduced intracellular lactate levels and decreased conversion of 13 Cpyruvate to 13 C lactate (21), it seems reasonable that the TMZ-induced decreases in intracellular lactate levels noted here resulted in the decreased pyruvate to lactate conversion in TMZ-treated animals. While direct proof of this linkage would require more complex methods such as diffusion-weighted spectroscopy to measure intracellular lactate levels in vivo (48, 49), the present data clearly show that PKM2 plays a key role in linking the DNA damage response to monitorable changes in pyruvate metabolism that in turn relate to drug efficacy.…”
Section: Discussionmentioning
confidence: 66%
“…Given the previously described connection between reduced intracellular lactate levels and decreased conversion of 13 Cpyruvate to 13 C lactate (21), it seems reasonable that the TMZ-induced decreases in intracellular lactate levels noted here resulted in the decreased pyruvate to lactate conversion in TMZ-treated animals. While direct proof of this linkage would require more complex methods such as diffusion-weighted spectroscopy to measure intracellular lactate levels in vivo (48, 49), the present data clearly show that PKM2 plays a key role in linking the DNA damage response to monitorable changes in pyruvate metabolism that in turn relate to drug efficacy.…”
Section: Discussionmentioning
confidence: 66%
“…Previous studies have quantified these non-diffusion related signal changes and corrected the diffusion weighted acquisitions accordingly [10,11]. To simplify the quantification of the diffusion coefficients, multiple interspersed normalization scans were acquired temporally close to the diffusion weighted scans and thereby eliminate the effects of these non-diffusion weighted signal changes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been several publications that have used diffusion weighted MR to measure the diffusion coefficients of hyperpolarized 13 C metabolites, in solution [10], in cell suspensions [11] and in vivo [1214]. These studies showed how changes in the ADCs could indicate the extra- and intracellular localization of the hyperpolarized 13 C metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to chemical shift [16, 73, 74, 75, 76, 77] and diffusion [78, 13, 79, 72, 80] sensitive imaging techniques, T 2 relaxometry could be a very useful tool for probing the microenvironment of hyperpolarized 13 C molecules in vivo since it yields high signal thus allowing for high resolution encoding.…”
Section: Discussionmentioning
confidence: 99%